STEM Teachers’ Professional Development through Scientist-Teacher-Students Partnership (STSP) (Jurnal Pendidikan IPA Indonesia, 2021)
Teachers are one of the most fundamental sources for the latest scientific information. However, many feel that teachers lack sufficient knowledge and skills to play this role, particularly in STEM, as STEM is related to more than one discipline. This study explores Scientist-Teacher-Students’ Partnership (STSP) as a professional development programme to enhance teachers’ understanding and conceptualization of the cutting-edge STEM knowledge and real-life applications of the STEM concepts. This study employed a qualitative research methodology, and it involved nine science teachers from four secondary schools and ten scientists from a university situated in Kuala Lumpur, Malaysia. Data were collected through observations made during activities and interviews. The collected data were analyzed using constant comparative data analysis techniques. Overall, the findings suggested that the tripartite collaboration brings educational benefits to all groups. From the perspective of teachers’ professional development, it was found that the partnership: (i) enhanced the teachers’ understanding of cutting-edge STEM knowledge; (ii) elevated their confidence and enthusiasm in STEM; and (iii) provide opportunities for information exchange and support through school-university networking. This study had promoted a more significant articulation of STSP as a mechanism for professional development in STEM education.